Personality characteristics, defense styles, borderline symptoms, and non-suicidal self-injury in first-episode major depressive disorder - Peng, Bo; Liao, Jiwu; Li, Yang; Jia, Guangbo; Yang, Jihui; Wu, Zhiwei; Zhang, Jian; Yang, Yingjia; Luo, Xinxin; Wang, Yao; Zhang, Yingli; Pan, Jiyang (Frontiers in Psychology, 2023)
Non-suicidal self-injury is commonly seen in depressed adolescents and is a high-risk factor leading to suicide. The psychological mechanisms underlying depression with NSSI are still unclear. The purpose of this study was to explore the differences in personality traits, defensive styles, and borderline symptoms among first-episode youth depressed patients with self-injury compared with depressed patients without self-injury and healthy populations. The current study recruited 188 participants, with 64 of them were depressed patients with self-injury and 60 of them were depressed patients without self-injury, and the rest of 64 participants were healthy populations. Eysenck Personality Questionnaire, the Defense Style Questionnaire, the short version of the Borderline Symptom List-23, the Beck Depression Inventory-II, and the Ottawa Self-Injury Inventory were used to assess all participants. This study found that depressed patients with self-injury presented more neuroticism, introversion, psychoticism, immature defenses, intermediate defenses, and borderline symptoms. Self-injury frequency was negatively correlated with mature defense styles and positively correlated with depressive symptoms and borderline symptoms. In depressed patients with and without self-injury, healthy populations, and total participants, borderline symptoms were positively correlated with neuroticism, immature defense styles, intermediate defense styles, and depressive symptoms. Psychoticism and depressive symptoms are risk factors for predicting non-suicidal self-injury in patients with depression.